2020
DOI: 10.32479/ijeep.10537
|View full text |Cite
|
Sign up to set email alerts
|

Fdi, Income, and Environmental Pollution in Indonesia

Abstract: The research aimed to evaluate the association of disposable income and environmental pollution on the investments measured using Foreign Direct Investment (FDI). The research was specific to the Indonesian economy. The research was secondary quantitative and the data was accumulated from World Bank. The time frame considered for this study ranged from 1960 to 2018. For statistical analysis, descriptive statistics, stationarity testing, ARDL assessment and Granger Causality have been used. The results unveiled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Employing the autoregressive distributive lag (ARDL) model, the study found that the inflow of FDI increases environmental degradation in Thailand, Malaysia, and the Philippines, whereas increase in foreign investment decreases environmental pollution in Indonesia and shows insignificant relation in Singapore. Bachri and Normelani ( 2020 ) evaluate the nexus of disposable income and environmental degradation on FDI in Indonesia utilized the ARDL and Granger causality test from 1960–2018. The study revealed that FDI has a significant impact on environmental pollution and income.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Employing the autoregressive distributive lag (ARDL) model, the study found that the inflow of FDI increases environmental degradation in Thailand, Malaysia, and the Philippines, whereas increase in foreign investment decreases environmental pollution in Indonesia and shows insignificant relation in Singapore. Bachri and Normelani ( 2020 ) evaluate the nexus of disposable income and environmental degradation on FDI in Indonesia utilized the ARDL and Granger causality test from 1960–2018. The study revealed that FDI has a significant impact on environmental pollution and income.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Merican et al ( 2007 ) found that the inflow of FDI increases environmental degradation in Thailand, Malaysia, and the Philippines, whereas increase in foreign investment decreases environmental pollution in Indonesia and shows insignificant relation in Singapore. Bachri and Normelani ( 2020 ) revealed that FDI has a significant impact on environmental pollution and income. H0: Renewable energy impacts favorable on both economic growth and environment quality …”
Section: Literature Reviewmentioning
confidence: 99%
“…The lack of environmental awareness and general information about the natural environment is the main issue causing the significant environmental damage that has taken place in Indonesia. Today's environmental harm is also influenced by human activity [27].…”
Section: Introductionmentioning
confidence: 99%
“…The rapid development of industry harms the environment, such as producing and discharging hazardous waste into the environment without prior processing. 1 Heavy metal waste, such as lead (Pb), cadmium (Cd), mercury (Hg), and chromium (Cr), are produced mainly through industrial activities. 2 According to the World Health Organization (WHO), chromium( vi ) waste is one of the carcinogenic pollutants to humans.…”
Section: Introductionmentioning
confidence: 99%